2003
DOI: 10.1074/jbc.m211763200
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Tumor Necrosis Factor α-induced Secreted Phospholipase A2 (sPLA2)-IIA Expression in Mesangial Cells by an Autocrine Loop Involving sPLA2 and Peroxisome Proliferator-activated Receptor α Activation

Abstract: In rat mesangial cells, exogenously added secreted phospholipases A 2 (sPLA 2 s) potentiate the expression of pro-inflammatory sPLA 2 -IIA first induced by cytokines like tumor necrosis factor-␣ (TNF␣) and interleukin-1␤. The transcriptional pathway mediating this effect is, however, unknown. Because products of PLA 2 activity are endogenous activators of peroxisome proliferatoractivated receptor ␣ (PPAR␣), we postulated that sPLA 2 s mediate their effects on sPLA 2 -IIA expression via sPLA 2 activity and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 67 publications
3
74
0
3
Order By: Relevance
“…Similar evidence was detected in culture media from human fibroblasts and chondrocytes (data not shown). High levels of sPLA 2 subtype, the so-called pancreatic-type sPLA 2 IB, are also found in the nondigestive tissues, including during acute pancreatitis (40,41), suggesting that group IB PLA 2 may also contribute to the pathophysiological effects in such conditions. In rat mesangial cells, exogenously added group IB PLA 2 can stimulate prostaglandin synthesis (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Similar evidence was detected in culture media from human fibroblasts and chondrocytes (data not shown). High levels of sPLA 2 subtype, the so-called pancreatic-type sPLA 2 IB, are also found in the nondigestive tissues, including during acute pancreatitis (40,41), suggesting that group IB PLA 2 may also contribute to the pathophysiological effects in such conditions. In rat mesangial cells, exogenously added group IB PLA 2 can stimulate prostaglandin synthesis (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…45 In this study, the contribution of exogenous secreted PLA 2 in the upregulation of PLA 2 IIA was calculated to be approximately 50%, whereas the remaining 50% was attributable to the cytokine stimulatory action. 45 Therefore, the secreted PLA 2 IIA released from HepG2 cells after proinflammatory cytokine stimulation may self-amplify the long-term total expression level of PLA 2 IIA. These phenomena may explain the discrepancies among 40% suppression on promoter activity, 40% suppression in mRNA expression level, and 96% suppression in protein expression level by UDCA in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…45 Beck et al 45 reported that PLA 2 IIA released from mesangial cells by TNF-␣ stimulates its own expression via an autocrine loop involving cytosolic PLA 2 and peroxisome proliferators-activated receptor ␣. 45 In this study, the contribution of exogenous secreted PLA 2 in the upregulation of PLA 2 IIA was calculated to be approximately 50%, whereas the remaining 50% was attributable to the cytokine stimulatory action. 45 Therefore, the secreted PLA 2 IIA released from HepG2 cells after proinflammatory cytokine stimulation may self-amplify the long-term total expression level of PLA 2 IIA.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborates recent results obtained in mesangial cells using heparinase-1. 19 Unlike this pharmacological compound, the use of sPLA2-IIA mutants eliminates the possibility of a release of truncated heparin sulfate chains from the cell surface. Proteoglycans function as a type of receptor system for fibroblast growth factor and for members of the opiate receptor family.…”
Section: Amandine Et Almentioning
confidence: 99%